The linkage of Islamic intellectual traditions in Bali with Malay world: Kampung Saren Jawa Manuscripts - Iswanto, Agus; Lukluil Maknun, Moch; Masfiah, Umi; Wajdi, Firdaus (Indonesian Journal of Islam and Muslim Societies, 2025)
This article intends to fill the lack of knowledge about Islamic intellectual traditions and networks in Bali by showing Islamic manuscripts found in an Islamic village in Karangasem Regency, namely Kampung Saren Jawa. Therefore, it is expected that the article can place the Islamic community in Bali and its Islamic intellectual tradition in the realm of discussion of Islamic scholarship in Indonesia, and Southeast Asia in general. The manuscripts were deemed copied around the 19th century and early 20th centuries. After describing various aspects of Islamic manuscripts found in Kampung Saren Jawa, such as materials of manuscripts, languages and scripts, colophons, and the contents of manuscript texts, we have argued that Islamic intellectual traditions in Bali relate to Islamic intellectual traditions outside of Bali, especially those that speak Malay and Javanese. An indication of the linkage of Islamic intellectual traditions in Bali with other regions, especially in the Malay world, is the discovery of several texts, which are the texts of Sufism, Fiqh, Tawhid, as well as religious literary texts written by famous scholars in the Malay world and has become popular texts until now